Regulation of copper transport into and within Arabidopsis thaliana chloroplasts: a focus on copper transport proteins - Gogolin, Kathryn Amy, author; Pilon, Marinus, advisor (Colorado State University. Libraries, 2007)
Copper is an essential micronutrient that is required for the biological processes of photosynthesis and respiration. Nutrients, such as copper, must travel long distances through several organs and across many membranes before they are incorporated into target enzymes. Plastocyanin is a small, copper containing protein that is located within the thylakoid lumen and is vital for photosynthetic activity in higher plants. In addition chloroplasts contain a second target for copper, the superoxide dismutase enzyme CSD2. Although copper is essential it can also be toxic to the cell, therefore there is tight regulation of ion transport. The objective of the research conducted here is to develop a better understanding of copper homeostasis in plant cells. By focusing on the proteins that are involved in the transport of copper new insight can be gained on the delivery pathways of this metal. In this dissertation, I further characterize P-type ATPase of Arabidopsis 1 (PAA1) and P-type ATPase of Arabidopsis 2 (PAA2). An Arabidopsis Copper Chaperone for Cu,Zn Superoxide dimustase (CCS) is identified as a functional homolog of the yeast copper chaperone for Cu,Zn superoxide dimustase (Ccs1/Lys7). I study the effects of altered CCS expression on copper homeostasis in a plant system and I determine that the Heavy Metal Associated 1 transporter functions to transport a metal other than Cu(I) across the chloroplast envelope which affects photosynthetic activity. Finally, I completed a comprehensive analysis of copper transport protein-protein interactions in Arabidopsis studied by the yeast two-hybrid system. With the data gathered here, I propose several new models for copper homeostasis in Arabidopsis. I suggest that there is regulation of Fe Superoxide Dismutase (FeSOD), CCS, and CSD2 in the chloroplast which is controlled by metal cofactor availability, specifically copper. By utilizing the yeast two-hybrid technique, I have identified two new possible delivery pathways for copper. I believe that CCS can deliver copper to Heavy Metal Associated 5 to aid in cell detoxification or possible long distance transport of the ion. Additionally, I propose that copper is transported directly from PAA1 to PAA2 in the chloroplast for delivery to plastocyanin.
Keywords: chloroplasts; copper; ion transport; plant biology; plastocyanin; superoxide dismutase; botany; cellular biology